Limited nucleotide changes of HIV-1 subtype B Rev response element in China affect overall Rev-RRE activity and viral replication - Shi, Yuting; Han, Jingwan; Zhu, Bo; Liu, Zhi; Liang, Qingmiao; Lan, Chunlin; Li, Zhengyang; Li, Hanping; Liu, Yongjian; Jia, Lei; Li, Tianyi; Wang, Xiaolin; et al. (Frontiers in Microbiology, 2022)
The HIV-1 Rev response element (RRE) is a cis-acting RNA element that facilitates the nuclear export of mRNA-containing introns by binding specifically to the Rev protein, enabling a critical step in the viral replication cycle. This study aims to determine the subtype-specific loci of HIV-1 subtype B RRE circulating in China and to analyze their effects on Rev-RRE function and HIV-1 replication. We amplified 71 HIV-1 subtype B RRE full-length sequences from the HIV patients' blood samples collected in China, analyzed the subtype-specific loci on them by comparing them with subtype B in the United States, and predicted their RNA secondary structures. Rev-RRE activity assay was used to test the binding activity of Rev and different RREs. Infectious clones were mutated to test the effect of the subtype-specific loci on replication capacity. In this study, two sites were determined to be the subtype-specific loci of HIV-1 subtype B RRE circulating in China. Both site 186 and site 56-57insAAC can significantly increase the viral mRNA transcription and Rev-RRE activity, but only the site 186 can significantly improve viral replication ability. Collectively, the subtype-specific loci of subtype B RRE circulating in China have a significant effect on the Rev-RRE activity and viral replication. This study investigates the subtype-specific loci of RRE, which are unique to retroviruses and essential for viral replication, and will help to explore the reasons why subtype B circulating in China is more widespread and persistent than American subtype B in China at the genetic level, and will provide theoretical support for the development of more inclusive detection and treatment methods for subtype B circulating in China. At the same time, it will also provide insight into the impact of different subtype HIV-1 genetic characteristics on viral replication.